PENDIDIKAN INKLUSIF SEBAGAI STRATEGI KEADILAN SOSIAL DI SEKOLAH DASAR ISLAM TERPADU ALAM TALAGO - Muhammad Khairul Hazli; Akmaluz Zikri; Wahidah Fitriani (Jurnal Al-Fatih, 2025)
This study aims to describe the implementation of inclusive education as a social justice strategy at SD IT Alam Talago. Inclusive education is seen as an important approach in ensuring the rights of every student to receive equal educational services without discrimination, especially for students with diverse learning needs. The main problem in this study relates to how the school applies the principles of inclusivity in learning and the challenges faced in its implementation. This study uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The research informants consisted of class teachers, assistant teachers, and the principal who were selected purposively. Data were analyzed using thematic analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that SD IT Alam Talago has implemented inclusive education through adaptation of learning methods, task differentiation, the use of varied media, and the provision of special assistance for students in need. In addition, the school has built a positive culture that emphasizes acceptance of diversity, collaboration between teachers, and parental involvement. However, obstacles still encountered are limited supporting facilities and differences in teacher competency in handling special needs. Overall, inclusive education at SD IT Alam Talago has been effective as a social justice strategy in creating a fair, friendly, and inclusive learning environment for all students.